PERBANDINGAN KADAR ASAM URAT PADA SUBYEK OBES DAN NON-OBES DI FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI MANADO - Rau, Elim; Ongkowijaya, Jeffrey; Kawengian, Ventje (e-CliniC, 2015)
Abstract: Uric acid is the end product of purine metabolism. Circulating uric acid in the human body is produced by the body (endogenous uric acid) as well as derived from food (exogenous uric acid). Normal serum uric acid level is <7.0 mg / dL in men and <6.0 in women. Obesity can be defined as excess body fat. One of the markers used for body fat content is body mass index (BMI). This study aimed to compare the levels of uric acid in obese and non-obese subjects. This was an analytical study with a cross sectional design. The population is students of Faculty of Medicine University of Sam Ratulangi Manado. Samples were male students of batch 2013. There were 42 male students, consisted of 21 obese and 21 non-obese students. The results showed that the average of uric acid levels in obese group was 8.05 mg/dL and in non-obese group 6.63 mg/dL. In the obese group, 67% had an increase in uric acid level meanwhile in the non-obese group only 38%. The statistical test showed a sig 0,009. Conclusion: In this study, the average of uric acid level in obese group was significantly higher than in the non-obese group. However, there were students with either normal or high uric acid levels in both groups.Keywords: uric acid, obeseAbstrak: Asam urat merupakan produk akhir metabolisme purin. Asam urat yang beredar di dalam tubuh manusia di produksi sendiri oleh tubuh (asam urat endogen) dan berasal dari makanan (asam urat eksogen). Normalnya kadar asam urat serum <7,0 mg/dL pada pria dan <6,0 mg/dL pada wanita. Obesitas dapat di definisikan sebagai kelebihan lemak tubuh. Penanda kandungan lemak tubuh yang digunakan ialah indeks masa tubuh (IMT). Penelitian ini bertujuan untuk mengetahui perbandingan kadar asam urat pada subyek obes dan non obes. Penelitian ini bersifat analitik dengan pendekatan potong lintang. Populasi penelitian ialah mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado. Sampel idalah mahasiswa pria angkatan 2013 dan didapatkan 42 orang yang terbagi atas 21 obes dan 21 non obes. Hasil penelitian memperlihatkan rerata kadar asam urat pada obes 8,05 mg/dL dan pada non-obes 6,63 mg/dL. Peningkatan kadar asam urat ditemukan 67% pada kelompok obes dan 38% pada kelompok non-obes. Uji statistik menunjukkan nilai sig 0,009. Simpulan: Pada penelitian ini rerata kadar asam urat pada kelompok obes lebih tinggi secara bermakna daripada kelompok non-obes. Walaupun demikian, pada kedua kelompok ditemukan mahasiswa dengan kadar asam urat normal maupun meningkat.Kata kunci: asam urat, obesitas